2005
DOI: 10.1590/s0034-70942005000600004
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia pós-operatória com bloqueio bilateral do nervo pudendo com bupivacaína S75:R25 a 0,25%: estudo piloto em hemorroidectomia sob regime ambulatorial

Abstract: Bilateral pudendal nerves block oriented by nerve stimulator provides excellent analgesia with low need for opioids, without local or systemic complications and without urinary retention. Controlled studies might be able to show whether this should be the first analgesic option for hemorrhoidectomies. Perineal anesthesia lasting 20.21 hours shall induce further studies with stimulator-oriented pudendal block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 7 publications
0
6
0
3
Order By: Relevance
“…In brachial plexus block, the enantiometric mixture (S75:R25) is a safer alternative if compared to racemic bupivacaine, due to its lower toxicity 7 . Based on a pilot study that reported reduction of postoperative pain with average analgesia of 24 hours 8 , this prospective, randomized, double-blind study was conducted to investigate the analgesia produced with bilateral pudendal blockade using levobupivacaine enantiomeric excess (S75:R25), compared to the method commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…In brachial plexus block, the enantiometric mixture (S75:R25) is a safer alternative if compared to racemic bupivacaine, due to its lower toxicity 7 . Based on a pilot study that reported reduction of postoperative pain with average analgesia of 24 hours 8 , this prospective, randomized, double-blind study was conducted to investigate the analgesia produced with bilateral pudendal blockade using levobupivacaine enantiomeric excess (S75:R25), compared to the method commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…There was no statistical difference between the groups in this respect. Complications such headache (4) and bladder function disorders (6) have been described in relation to SA, but no such complications have been reported with LA. Complications relating to colon reconstruction, such as prolonged ileus and dehiscence of anastomosis have been described in other studies (2) .…”
Section: Discussionmentioning
confidence: 99%
“…A anestesia dos nervos pudendos é uma boa técnica nas cirurgias anorretais, cirurgias perineais e analgesia de parto 8,9 . Imbelloni e col. 10 avaliaram a analgesia com bloqueio dos nervos pudendos em pacientes submetidos a hemorroidectomia sob raquianestesia, utilizando estimulador de nervos pela técnica transperineal. No estudo, 51% dos pacientes não necessitou de nenhum analgésico no pós-operatório e 77% deles consideraram a técnica excelente.…”
Section: Discussionunclassified
“…The anesthesia of the pudend nerves is a good technique in the anorectal surgeries, in the perineal surgeries and labor analgesia 8,9 . Imbelloni et al 10 evaluated the analgesia with the blockade of the pudend nerves in patients submitted to hemorrhoidectomy under spinal anesthesia, using a nerve stimulator through the transperineal technique. In the study, 51% of the patients did not need any postoperative analgesic and 77% of the patients considered it an excellent technique.…”
Section: Discussionmentioning
confidence: 99%